Preparation method of boron-doped nano polycrystalline diamond

Through the fine treatment of high-purity scale graphite and uniform doping of boron source, combined with the H2 treatment and sintering process of high-temperature vacuum furnace, the problem of uneven distribution of boron-doped nano-polycrystal diamond boron elements is solved, and the stability of product performance and the reduction of synthesis conditions is achieved, achieving the purpose of cost saving.

CN119710916APending Publication Date: 2025-03-28ZHENGZHOU ZHONGNAN JETE SUPERABRASIVES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411935162.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the existing boron doped nano-polycrystal diamond preparation method, uneven distribution of boron sources leads to uneven distribution of boron elements, affecting the stability of product performance, and the pressure and temperature required for synthesis under high temperature and high pressure conditions are higher and the cost is higher.

Method used

High-purity scale graphite is used as raw material, and graphite powder with uniform particle size is obtained through screening, ball milling, fine processing, grading and other processes, and the boron source is mixed with the solvent to control the boron concentration, improve the boron doping uniformity, and H2 treatment and sintering are carried out through a high-temperature vacuum furnace to reduce the pressure and temperature required for synthesis.

Benefits of technology

The uniformity of the boron-doped nano-polycrystalline diamond boron element distribution is achieved, the heat resistance, oxidation resistance and chemical inertia of the product are improved, the pressure and temperature required for synthesis are reduced, and the cost is saved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710916A_ABST
    Figure CN119710916A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of boron-doped nano polycrystalline diamond, and relates to the technical field of preparation methods of artificial diamonds, and the preparation method comprises the following steps: carrying out grain size screening on high-purity crystalline flake graphite, carrying out ball milling for 12-24 hours, then carrying out size grading again, selecting 10000-12000 meshes, and then precipitating; removing impurities from the precipitate, washing to be neutral, and drying for later use; mixing a boron source with a solvent, and stirring to obtain a boron-containing solution; the preparation method comprises the following steps: mixing graphite powder and a boron-containing solution in ethanol to obtain a mixed solution, and drying the mixed solution in a vacuum freeze dryer to obtain boron-doped graphite powder; pressing the boron-doped graphite powder into a synthetic core column; and carrying out vacuum drying treatment on the synthesized core column and then carrying out high-temperature and high-pressure sintering to obtain the boron-doped nano polycrystalline diamond. According to the preparation method of the boron-doped nano polycrystalline diamond, the controllability of the boron doping concentration is realized in a doping mode that the graphite powder with uniform granularity and high forming density is matched with the liquid inorganic boron, so that the boron-doped nano polycrystalline diamond with excellent performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of artificial diamond preparation methods, and in particular to a method for preparing boron-doped nano polycrystalline diamond. Background Art

[0002] Polycrystalline diamond has high hardness and wear resistance. It overcomes the shortcomings of single-crystal diamond anisotropy and {111} crystal plane dissociation and destruction, and is widely used in many fields such as aerospace, electronics, construction, gem processing, oil drilling and geological exploration. There are two main ways to prepare polycrystalline diamond under high temperature and high pressure: one is to synthesize diamond from graphite and then sinter it from diamond powder; the other is to directly transform graphite into nano-polycrystalline diamond, which is formed by direct transformation of graphite under ultra-high pressure and high temperature conditions of 15-20GPa and 2300-2600K. The overall performance of polycrystalline diamond synthesized by the second method is far superior to the first one, which is the current and future development direction. However, diamond has poor heat resistance and cannot be used for ferrous metal processing. For this reason, people improve the performance of diamond by adding boron. Boron-doped diamond has higher heat resistance, good chemical inertness, excellent semiconductor performance, excellent electrical properties, good impact toughness, wear resistance and compressive resistance. How to synthesize high-quality boron-doped nano-polycrystalline diamond has become a goal pursued by manufacturers and users. At present, boron-doped nano-polycrystalline diamond is mostly synthesized by adding a certain amount of boron source to graphite and mixing it evenly, and then directly converting it under high temperature and high pressure. However, this method has high requirements on the purity of raw materials and the uniformity of the mixed materials. The boron content of the produced boron-doped nano-polycrystalline diamond fluctuates greatly and is unevenly distributed, resulting in unstable performance of boron-doped nano-polycrystalline diamond, which is not conducive to its use and promotion. Summary of the invention

[0003] The main purpose of the present invention is to provide a method for preparing boron-doped nano-polycrystalline diamond to solve the technical problem that uneven distribution of boron source leads to uneven distribution of boron elements in the produced boron-doped nano-polycrystalline diamond, and can greatly reduce the pressure and temperature required for the synthesis of high-quality boron-doped nano-polycrystalline diamond, thereby achieving the purpose of stable conversion and cost saving.

[0004] To achieve the above object, the present invention provides the following technical solutions: A method for preparing boron-doped nano-polycrystalline diamond comprises the following steps: 1) Screen the high-purity flake graphite for grain size, and take 500-600 mesh as the sample to be processed; 2) Place the sample to be processed in a ball mill, add alcohol and mix into a paste, then add steel balls and mill on a ball mill for 12 to 24 hours; 3) After the ball milling is completed, the ball-milled graphite is flushed into a beaker with pure water, and the particle size is reclassified, and 10000-12000 mesh is selected for precipitation; 4) Pour away the clear water after precipitation, add hydrochloric acid and boil on an electric furnace for half an hour to further remove impurities, cool naturally and wash with pure water until neutral, and dry the graphite powder obtained after precipitation in a vacuum drying oven for later use; 5) mixing the boron source and the solvent in a weight ratio of (10:90) to (30:70), stirring at 20 to 70° C. for 60 to 90 minutes to obtain a boron-containing solution; 6) mixing the graphite powder in 4) and the boron-containing solution in 5) in ethanol, wherein the weight ratio of the graphite powder to the boron-containing solution is (95:5) to (85:15), stirring for 60 to 90 minutes after mixing, and drying the mixed solution in a vacuum freeze dryer to obtain boron-doped graphite powder; 7) treating the boron-doped graphite powder in 6) with H2 in a high-temperature vacuum furnace at 1000-1500° C. for 1-3 hours, taking it out, and pressing it into a synthetic core column of the required size using a mold; 8) The pressed synthetic core column is vacuum dried in a high temperature vacuum furnace at 600°C for 1 to 2 hours and vacuum packaged for standby use; 9) The synthetic core column is subjected to high temperature and high pressure sintering, the pressure of the high temperature and high pressure sintering is 10-18 GPa, and the sintering temperature is 1800-2100°C. After the pressure is released, the obtained sample is subjected to surface grinding and deburring treatment in sequence to obtain boron-doped nano-polycrystalline diamond.

[0005] Preferably, the purity of the high-purity flake graphite in step 1 is ≥99.99%.

[0006] Preferably, the mass of the steel balls added in step 2 is 10 to 20 times the mass of the flake graphite of the sample to be processed.

[0007] Preferably, in step 2, the steel balls are of three sizes: 6 mm, 8 mm, and 10 mm and are mixed in a mass ratio of 2:3:5.

[0008] Preferably, the ball mill used in step 2 is an iron ball mill.

[0009] Preferably, the drying operation in the vacuum drying oven in step 4 is: drying the graphite powder at 120-150° C. for 4-8 hours.

[0010] Preferably, in step 5, the solvent is one or more of methanol, ethanol, n-butanol, and acetone; the boron source is one or more of boric acid, boron oxide, and boron element; and the grain size of the boron source is preferably 0.5 to 1 μm.

[0011] Preferably, the pressure for forming the synthetic core column in step 7 is preferably 400-600 MPa, more preferably 450-550 MPa, and the holding time is preferably 30-60 s, more preferably 40-50 s.

[0012] Preferably, the high temperature vacuum furnace in step 7 applies pressure to the high temperature and high pressure sintering pressure within 10 to 24 hours in advance; the heating rate from room temperature to the sintering temperature is preferably 10°C / min; and the holding time for high temperature and high pressure sintering is preferably 10 to 30 minutes.

[0013] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses high-purity flake graphite as raw material, and obtains graphite powder with uniform particle size and high molding density through screening, ball milling, fine treatment, classification and other processes. The graphitization degree, porosity (bulk density), ash content (purity), resistivity and crystal structure of the graphite powder can greatly reduce the pressure and temperature required for growing high-quality polycrystalline diamond synthesis.

[0014] 2. The present invention changes the doping mode of inorganic boron from solid to liquid, improves the problem of poor doping uniformity of solid boron source, controls the boron concentration in the solution by selecting the boron source and solvent and controlling the temperature, thereby achieving controllability of the boron doping concentration and further realizing uniform boron doping.

[0015] 3. The boron-doped nano-polycrystalline diamond prepared by the present invention has uniform grain size, stable and uniform boron content, high thermal shock value, and its heat resistance, oxidation resistance, chemical inertness and other properties are greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a transmission electron microscope photo of boron-doped nano-polycrystalline diamond in Example 4; Figure 2 It is the Knoop hardness of the boron-doped nano-polycrystalline diamond in Example 4. DETAILED DESCRIPTION

[0017] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods. Example

[0018] This embodiment provides a method for preparing boron-doped nano-polycrystalline diamond, comprising the following steps: (1) Screen the flake graphite with a purity of ≥99.99% and take 500-600 mesh as the sample to be processed; (2) The sample to be processed obtained in (1) is placed in an iron ball mill, and alcohol is added to mix into a paste. Then, steel balls are added. The mass of the steel balls is 10 times the mass of the flake graphite of the sample to be processed. The steel balls are of three sizes: 6 mm, 8 mm, and 10 mm, and are mixed in a mass ratio of 2:3:5. The mixture is ball milled in a ball mill for 24 h. (3) After the ball milling is completed, the ball-milled graphite is flushed into a beaker with pure water and re-graded to select 10000-12000 mesh and then precipitated; (4) Pour away the clear water after precipitation, add hydrochloric acid and boil on an electric furnace for half an hour to further remove impurities, cool naturally and wash with pure water until neutral, and dry the graphite powder obtained after precipitation in a vacuum drying oven at 120°C for 8 hours for later use; (5) mixing boric acid and ethanol in a weight ratio of 10:90, stirring at 20° C. for 60 minutes to obtain a boron-containing solution; (6) mixing the graphite powder in (4) and the boron-containing solution in (5) in ethanol, wherein the weight ratio of the graphite powder to the boron-containing solution is 95:5, stirring for 60 minutes after mixing, and drying the mixed solution in a vacuum freeze dryer to obtain boron-doped graphite powder; (7) treating the boron-doped graphite powder in (6) with H2 for 3 h at 1500°C in a high-temperature vacuum furnace, taking it out, and pressing it into a synthetic core column of the required size using a mold; (8) The pressed synthetic core column is vacuum dried in a high temperature vacuum furnace at 600°C for 2 hours and vacuum packaged for standby use; (9) The synthetic core column is subjected to high temperature and high pressure sintering, the pressure of high temperature and high pressure sintering is 12GPa, and the sintering temperature is 1800℃. After the pressure is released, the obtained sample is subjected to surface grinding and deburring treatment in sequence to obtain boron-doped nano-polycrystalline diamond. The Vickers hardness of the prepared boron-doped nano-polycrystalline diamond is 90.94~95.91GPa. Example

[0019] This embodiment provides a method for preparing boron-doped nano-polycrystalline diamond, comprising the following steps: (1) Screen the flake graphite with a purity of ≥99.99% and take 500-600 mesh as the sample to be processed; (2) Place the sample to be processed obtained in (1) into an iron ball mill, add alcohol and mix into a paste, then add steel balls. The mass of the steel balls is 20 times the mass of the flake graphite of the sample to be processed. The steel balls are of three sizes: 6 mm, 8 mm, and 10 mm and are mixed in a mass ratio of 2:3:5. The balls are ball milled on a ball mill for 12 h. (3) After the ball milling is completed, the ball-milled graphite is flushed into a beaker with pure water and re-graded to select 10000-12000 mesh and then precipitated; (4) Pour away the clear water after precipitation, add hydrochloric acid and boil on an electric furnace for half an hour to further remove impurities, cool naturally and wash with pure water until neutral, and dry the graphite powder obtained after precipitation in a vacuum drying oven at 120°C for 8 hours for later use; (5) mixing boron oxide and n-butanol in a weight ratio of 20:80, stirring at 50° C. for 90 min, and obtaining a boron-containing solution; (6) mixing the graphite powder in (4) and the boron-containing solution in (5) in ethanol, wherein the weight ratio of the graphite powder to the boron-containing solution is 95:5, stirring for 90 minutes after mixing, and drying the mixed solution in a vacuum freeze dryer to obtain boron-doped graphite powder; (7) treating the boron-doped graphite powder in (6) with H2 for 2 h at 1500°C in a high-temperature vacuum furnace, taking it out, and pressing it into a synthetic core column of the required size using a mold; (8) The pressed synthetic core column is vacuum dried in a high temperature vacuum furnace at 600°C for 1 hour and vacuum packaged for standby use; (9) The synthetic core column is subjected to high temperature and high pressure sintering, the pressure of high temperature and high pressure sintering is 16GPa, and the sintering temperature is 1800℃. After the pressure is released, the obtained sample is subjected to surface grinding and deburring treatment in sequence to obtain boron-doped nano-polycrystalline diamond. The Vickers hardness of the prepared boron-doped nano-polycrystalline diamond is 84.23~94.35GPa. Example

[0020] This embodiment provides a method for preparing boron-doped nano-polycrystalline diamond, comprising the following steps: (1) Screen the flake graphite with a purity of ≥99.99% and take 500-600 mesh as the sample to be processed; (2) Place the sample to be processed obtained in (1) into an iron ball mill, add alcohol and mix into a paste, then add steel balls. The mass of the steel balls is 15 times the mass of the flake graphite of the sample to be processed. The steel balls are of three sizes: 6 mm, 8 mm, and 10 mm and are mixed in a mass ratio of 2:3:5. The mixture is ball milled on a ball mill for 18 h. (3) After the ball milling is completed, the ball-milled graphite is flushed into a beaker with pure water and re-graded to select 10000-12000 mesh and then precipitated; (4) Pour away the clear water after precipitation, add hydrochloric acid and boil on an electric furnace for half an hour to further remove impurities, cool naturally and wash with pure water until neutral, and dry the graphite powder obtained after precipitation in a vacuum drying oven at 150°C for 8 hours for use; (5) Mixing boron element and acetone solvent in a weight ratio of 10:90, stirring at 20°C for 90 min to obtain a boron-containing solution; (6) mixing the graphite powder in (4) and the boron-containing solution in (5) in ethanol, wherein the weight ratio of the graphite powder to the boron-containing solution is 90:10, stirring for 90 minutes after mixing, and drying the mixed solution in a vacuum freeze dryer to obtain boron-doped graphite powder; (7) treating the boron-doped graphite powder in (6) with H2 in a high-temperature vacuum furnace at 1500°C for 2 h, taking it out, and pressing it into a synthetic core column of the required size using a mold; (8) The pressed synthetic core column is vacuum dried in a high temperature vacuum furnace at 600°C for 2 hours and vacuum packaged for standby use; (9) The synthetic core column is subjected to high temperature and high pressure sintering, the pressure of high temperature and high pressure sintering is 16GPa, and the sintering temperature is 2100℃. After the pressure is released, the obtained sample is subjected to surface grinding and deburring treatment in sequence to obtain boron-doped nano-polycrystalline diamond. The Vickers hardness of the prepared boron-doped nano-polycrystalline diamond is 100.32~105.41GPa. Example

[0021] This embodiment provides a method for preparing boron-doped nano-polycrystalline diamond, comprising the following steps: (1) Screen the flake graphite with a purity of ≥99.99% and take 500-600 mesh as the sample to be processed; (2) The sample to be processed obtained in (1) is placed in an iron ball mill, and alcohol is added to mix into a paste. Then, steel balls are added. The mass of the steel balls is 20 times the mass of the flake graphite of the sample to be processed. The steel balls are of three sizes: 6 mm, 8 mm, and 10 mm, and are mixed in a mass ratio of 2:3:5. The mixture is ball milled in a ball mill for 24 h. (3) After the ball milling is completed, the ball-milled graphite is flushed into a beaker with pure water and re-graded to select 10000-12000 mesh and then precipitated; (4) Pour away the clear water after precipitation, add hydrochloric acid and boil on an electric furnace for half an hour to further remove impurities, cool naturally and wash with pure water until neutral, and dry the graphite powder obtained after precipitation in a vacuum drying oven at 150°C for 8 hours for use; (5) Mixing a boron source (boric acid, boron element) with a solvent (ethanol, n-butanol), wherein the weight ratio of boric acid to boron element is 1:1, the weight ratio of ethanol to n-butanol is 1:3, and the weight ratio of the boron source to the solvent is 10:90. After mixing, stirring at 50°C for 90 minutes can obtain a boron-containing solution; (6) mixing the graphite powder in (4) and the boron-containing solution in (5) in ethanol, wherein the weight ratio of the graphite powder to the boron-containing solution is 90:10, stirring for 90 minutes after mixing, and drying the mixed solution in a vacuum freeze dryer to obtain boron-doped graphite powder; (7) treating the boron-doped graphite powder in (6) with H2 for 3 h at 1500°C in a high-temperature vacuum furnace, taking it out, and pressing it into a synthetic core column of the required size using a mold; (8) The pressed synthetic core column is vacuum dried in a high temperature vacuum furnace at 600°C for 2 hours and vacuum packaged for standby use; (9) The synthetic core column is subjected to high temperature and high pressure sintering, the pressure of high temperature and high pressure sintering is 18GPa, and the sintering temperature is 2100℃. After the pressure is released, the obtained sample is subjected to surface grinding and deburring treatment in sequence to obtain boron-doped nano-polycrystalline diamond. The Vickers hardness of the prepared boron-doped nano-polycrystalline diamond is 105.56~110.78GPa.

[0022] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing boron-doped nano-polycrystalline diamond, characterized in that: The following steps are involved: 1) Screen the high-purity flake graphite for grain size, and take 500-600 mesh as the sample to be processed; 2) Place the sample to be processed in a ball mill, add alcohol and mix into a paste, then add steel balls and mill on a ball mill for 12 to 24 hours; 3) After the ball milling is completed, the ball-milled graphite is flushed into a beaker with pure water, and the particle size is reclassified, and 10000-12000 mesh is selected for precipitation; 4) Pour away the clear water after precipitation, add hydrochloric acid and boil on an electric furnace for half an hour to further remove impurities, cool naturally and wash with pure water until neutral, and dry the graphite powder obtained after precipitation in a vacuum drying oven for later use; 5) mixing the boron source and the solvent in a weight ratio of (10:90) to (30:70), stirring at 20 to 70° C. for 60 to 90 minutes to obtain a boron-containing solution; 6) mixing the graphite powder in 4) and the boron-containing solution in 5) in ethanol, wherein the weight ratio of the graphite powder to the boron-containing solution is (95:5) to (85:15), stirring for 60 to 90 minutes after mixing, and drying the mixed solution in a vacuum freeze dryer to obtain boron-doped graphite powder; 7) treating the boron-doped graphite powder in 6) with H2 in a high-temperature vacuum furnace at 1000-1500° C. for 1-3 hours, taking it out, and pressing it into a synthetic core column of the required size using a mold; 8) The pressed synthetic core column is vacuum dried in a high temperature vacuum furnace at 600°C for 1 to 2 hours and vacuum packaged for standby use; 9) The synthetic core column is subjected to high temperature and high pressure sintering, the pressure of the high temperature and high pressure sintering is 10-18 GPa, and the sintering temperature is 1800-2100°C. After the pressure is released, the obtained sample is subjected to surface grinding and deburring treatment in sequence to obtain boron-doped nano-polycrystalline diamond.

2. The method for preparing boron-doped nano-polycrystalline diamond according to claim 1, characterized in that: The purity of the high-purity flake graphite in step 1 is ≥99.99%.

3. The method for preparing boron-doped nano-polycrystalline diamond according to claim 2, characterized in that: The mass of the steel balls added in step 2 is 10 to 20 times the mass of the flake graphite of the sample to be processed.

4. The method for preparing boron-doped nano-polycrystalline diamond according to claim 3, characterized in that: In step 2, the steel balls are of three sizes: 6 mm, 8 mm, and 10 mm, and are mixed in a mass ratio of 2:3:

5.

5. The method for preparing boron-doped nano-polycrystalline diamond according to claim 4, characterized in that: The ball mill used in step 2 is an iron ball mill.

6. The method for preparing boron-doped nano-polycrystalline diamond according to claim 5, characterized in that: The drying operation in the vacuum drying oven in step 4 is as follows: drying the graphite powder at 120-150° C. for 4-8 hours.

7. The method for preparing boron-doped nano-polycrystalline diamond according to claim 6, characterized in that: In step 5, the solvent is one or more of methanol, ethanol, n-butanol, and acetone; the boron source is one or more of boric acid, boron oxide, and boron element; and the boron source has a grain size of preferably 0.5 to 1 μm.

8. The method for preparing boron-doped nano-polycrystalline diamond according to claim 7, characterized in that: The pressure for forming the synthetic core column in step 7 is preferably 400-600 MPa, more preferably 450-550 MPa, and the holding time is preferably 30-60 s, more preferably 40-50 s.

9. The method for preparing boron-doped nano-polycrystalline diamond according to claim 8, characterized in that: In step 7, the high-temperature vacuum furnace applies pressure to the high-temperature and high-pressure sintering pressure within 10 to 24 hours in advance; the heating rate from room temperature to the sintering temperature is preferably 10°C / min; and the holding time for high-temperature and high-pressure sintering is preferably 10 to 30 minutes.